Methodology for evaluating the effectiveness of anti-corruption activities in the military sector under conditions of ensuring financial security - Kryshtanovych, Myroslav; Криштанович, Мирослав; Nazarenko, Oleksandr; Назаренко, Олександр; Bazyka, Serhii; Базика, Сергій; Vasyliev, Oleksii; Васильєв, Олексій; Munko, Anna; Мунько, Анна Юріївна; Panas, Yaroslav; Панас, Ярослав (ТОВ «ФІНТЕХАЛЬЯНС», 2025)
The military sector has undergone radical changes since the full-scale invasion in Feb-ruary 2022. Along with physical transformations, there have been financial ones as well. The volumes of financial provision for military affairs have increased dramatically, and thus, the temptation for corrupt actions has risen. Cases of corruption in the military sector are constantly being traced in information sources. In such circumstances, it is crucial to evaluate current anti-corruption measures to ensure financial security. The purpose of this article is to evaluate the effectiveness of anti-corruption activities in the military sector. The object of the article is an anti-corruption activity in the military sphere. In this context, the scientific task is to improve the methodology for evaluating the effectiveness of anti-corruption activities in the military sector. The task of the article is to promote anti-corruption activity in the military sector through the proposal of a new method, which will facilitate the formation of an informational basis for ensuring financial security. A methodology for evaluating the effectiveness of anti-corruption ac-tivities in the military sphere has been proposed. The basis is the coefficient evaluation method, which is used to describe methods that are based on the application of certain coefficients for determining assessments or ranking objects, alternatives, or parameters. The proposed methodology lays the foundation for forming an informational basis re-garding ensuring financial security. Its practical application was carried out based on three military units, but a comprehensive evaluation remains a matter of further re-search. Limitations related to the fact that not all possible indicators and coefficients were properly involved. In the future, attention should also be paid to researching how new digital technologies affect the strengthening of corruption and its development. Cryptocurrency and artificial intelligence deserve special attention. Військова сфера радикально змінилася після повномасштабного вторгнення в лютому 2022 року. Разом із фізичними змінами відбулися й фінансові. Обсяги фінансового забезпечення військової справи зросли кардинально, й отже, зросла спокуса до корупційних дій. В інформаційних джерелах постійно простежуються випадки корупційних дій у військовій сфері. У таких умовах важливим є оцінювати поточні антикорупційні дії з метою забезпечення фінансової безпеки. Метою дослідження є здійснення оцінювання ефективності антикорупційної діяльності у військовій сфері. Об’єктом дослідження є антикорупційна діяльність у військовій сфері. При цьому наукове завдання полягає в тому, щоб удосконалити методику оцінювання ефективності антикорупційної діяльності у військовій сфері. Об’єктом дослідження є антикорупційна діяльність у військовій сфері через пропозицію нового методу, який сприятиме формуванню інформаційного підґрунтя для забезпечення фінансової безпеки. Запропоновано методику оцінювання ефективності антикорупційної діяльності у військовій сфері. В основі лежить коефіцієнтний метод оцінювання, який використовують для опису методів, які ґрунтуються на застосуванні певних коефіцієнтів для визначення оцінок або ранжування об’єктів, альтернатив чи параметрів. Запропонована методика закладає основу для формування інформаційного підґрунтя щодо забезпечення фінансової безпеки. Її практичне застосування здійснене на базі трьох військових частин, проте всеохоплююче оцінювання є питанням подальших досліджень. Обмеження стосувалися того факту, що не всі з можливих показників і коефіцієнтів були задіяні належним чином. У перспективі слід також приділити увагу дослідженню того, як нові цифрові технології впливають на посилення корупції та її розвиток. Особливої уваги заслуговують криптовалюта й штучний інтелект.
Методика оцінювання ефективності антикорупційної діяльності у військовій сфері в умовах забезпечення фінансової безпеки
Keywords: evaluation methodology; методика оцінювання; military sector; військова сфера; anti-corruption management; антикорупційне управління; financial security; фінансова безпека; state; держава; combating corruption; протидія корупції